Bacillus Calmette-Guerin-induced interleukin-12 did not additionally improve clinical and immunologic parameters in asthmatic children treated with sublingual immunotherapy - AKKOÇ, TUNÇ (WILEY, 2004)
Objective To evaluate the effect of bacillus Calmette-Guerin (BCG) as an adjuvant to specific sublingual immunotherapy (SLIT) on the cytokine profile of peripheral blood mononuclear cells (PBMCs) and clinical outcome. Methods Thirty-two children with asthma and rhinitis allergic to house dust mite (HDM) with negative purified protein derivative (PPD) skin test response were enrolled. After a run-in period of 8 weeks, patients were randomized to receive either SLIT only (n=16) or one dose of BCG immunization before initiation of SLIT (n=16) with a standardized Dermatophagoides pteronyssinus (D. pteronyssinus)+D. farinea 50/50 extract. PPD-negative asthmatics (n=5) allergic to HDM receiving inhaled therapy only were included for comparison of cytokine levels in PBMC cultures. Efficacy was assessed both at the end of run-in and 6 months of treatment periods with criteria including symptom, medication and quality-of-life (QoL) scores, IgE levels, lung function, provocation concentration (PC20), eosinophil count and skin prick tests. IL-4, IL-5, IL-10, IL-12, IL-13 and IFN-gamma levels were determined in antigen specifically and polyclonally stimulated PBMC cultures. Results Both treatment groups showed significant improvement at the end of 6 months for asthma and rhinitis scores and QoL, number of asthma attacks, amount of beta(2)-agonists, inhaled and intranasal steroids, blood eosinophil counts and PC20. Interestingly, phytohaemagglutinin (PHA)-stimulated IL-12 and D. pteronyssinus-stimulated IFN-gamma in PBMC were significantly higher in the treatment groups than controls. In addition, IL-12 levels in response to D. pteronyssinus and PHA stimulation were significantly higher in the SLIT+BCG group than the SLIT alone group and controls. Conclusion The present study demonstrates that successful SLIT is parallel to increased IFN-gamma production by PBMC. Although simultaneous BCG vaccination enhanced IL-12 production, it did not additionally improve the clinical outcome.
Keywords: bacillus Calmette-Guerin; IFN-gamma; IL-12; sublingual immunotherapy; KILLED MYCOBACTERIUM-BOVIS; HOUSE-DUST MITE; DOUBLE-BLIND; AIRWAY HYPERRESPONSIVENESS; DERMATOPHAGOIDES-PTERONYSSINUS; ORAL TOLERANCE; MURINE MODEL; T-HELPER; IL-12; INFLAMMATION